Reawakening the Developmental Origins of Cancer Through Transposable Elements - Lynch-Sutherland, Chiemi F.; Chatterjee, Aniruddha; Stockwell, Peter A.; Eccles, Michael R.; Macaulay, Erin C. (Frontiers in Oncology, 2020)
Transposable elements (TEs) have an established role as important regulators of early human development, functioning as tissue-specific genes and regulatory elements Functional TEs are highly active during early development, and interact with important developmental genes, some of which also function as oncogenes. Dedifferentiation is a hallmark of cancer, and is characterised by genetic and epigenetic changes that enable proliferation, self-renewal and a metabolism reminiscent of embryonic stem cells. There is also compelling evidence to support that the path to dedifferentiation in cancer can contribute to invasion and metastasis. TEs are frequently expressed in cancer. To this end, recent work has shown extensive recruitment of TE-derived promotors to drive expression of oncogenes and subsequently promote oncogenesis – a process termed onco-exaptation. Existing hypotheses suggest that these onco-exaptation events are cancer-specific and arise randomly due to the dysregulated and hypomethylated state of cancer cells and abundance of TEs across the genome. However, we suspect that exaptation-like events may not just arise due to chance activation of novel regulatory relationships as proposed previously, but as a result of the reestablishment of early developmental regulatory relationships. Thus, we hypothesise that onco-exaptation is associated with the epigenetic reawakening of early developmental TEs. We expect that this occurs as a result of the establishment of an epigenetic landscape in cancer that resembles that of the early development.